Issue of fairness in benchmarking teacher quality in Malaysia teaching standard: lessons for other countries - Abdullah, Nur Surayyah Madhubala (Human Resource Management Academic Research Society, 2019)
The issue of fairness in the use of student achievement in benchmarking teacher standard and hence, as a measure of teacher quality in Malaysian Teaching Standards (MTS) is highlighted. Through an examination of the idea of teacher standards in MTS and consideration of the issue of what should be an adequate measure of teacher performance, two observations are made. First, the use of student achievement to measure teacher standard and, hence their quality as teachers, raises an issue of fairness in the assessment of teacher performance. Second, setting a standard of producing an ideal person in MTS renders the standards questionable as a fair measure of teacher performance, considering the complexity of teaching and, learner diversity. Together the findings reveal two issue. First, what should be used to gauge teacher quality? Second, how should teacher quality be understood? Several possible implications for improving teacher quality within policy and teacher education programs are noted. Standards should be couched in reality of teachers and teaching to avoid unfair treatment of teachers. The paper offers policy makers, practitioners and teacher educators in other countries a brief overview of some challenges of ensuring policy or programs on teacher standards are socially just.